2017
DOI: 10.1155/2017/7526494
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatogastrostomy versus Pancreatojejunostomy: An Up-to-Date Meta-Analysis of RCTs

Abstract: Background A meta-analysis was conducted in order to provide an up-to-date comparison of pancreatogastrostomy (PG) and pancreatojejunostomy (PJ), after pancreatoduodenectomy (PD), in terms of clinically significant postoperative pancreatic fistula (POPF) and other postoperative complications. Methods This meta-analysis was conducted according to the PRISMA guidelines and the Cochrane Handbook for Systematic Reviews of Interventions. A systematic literature search in MEDLINE and Cochrane Central Register of Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Some meta-analyses [26][27][28] have shown a reduced incidence of insufficiency of the PG compared to PJ. PJ has been shown to be more physiological, as reduced incidence of impaired glucose tolerance, steatorrhea, and atrophic changes of the remaining pancreas have been reported in patients with PJ compared to patients with PG [29][30][31]. Nevertheless, it is hypothesized to adhere to well established surgical techniques to achieve best performance.…”
Section: Discussionmentioning
confidence: 99%
“…Some meta-analyses [26][27][28] have shown a reduced incidence of insufficiency of the PG compared to PJ. PJ has been shown to be more physiological, as reduced incidence of impaired glucose tolerance, steatorrhea, and atrophic changes of the remaining pancreas have been reported in patients with PJ compared to patients with PG [29][30][31]. Nevertheless, it is hypothesized to adhere to well established surgical techniques to achieve best performance.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a higher frequency of impaired glucose tolerance after PG has been reported compared to PJ during the follow-up period. Considering the function of the remnant pancreas, the use of only short-term results is not sufficient for comparison[34,49].…”
Section: Pancreaticoduodenectomymentioning
confidence: 99%
“…Some studies comparing PJ with PG showed no difference between these methods. 16 18 However, others showed that fewer postoperative fistulas develop after PG. 19 21 Therefore, we performed an up-to-date meta-analysis of randomized controlled trials (RCTs) to summarize the currently available evidence on PG versus PJ according to the newest 2016 ISGPS criteria.…”
mentioning
confidence: 99%